Salvadorean Refugee Women and Employment Creation Programmes in Costa Rica - Basok, Tanya (Refuge: Canada's Journal on Refugees, 1987)
As decades of political repression had by 1980 culminated in a full-scale civil war in El Salvador, thousands of its victims fled the country in search of haven. Costa Rica was viewed as one of the most politically stable and non-repressive countries of Central America and therefore many Salvadoreans asked this country for asylum. At the end of 1980, there were more than 2,000 refugees in Costa Rica and by March 1981, the figure had risen to over four thousand. Between 1980 and 1983 an average of 9,000 refugees per year arrived in Costa Rica.